Advancing perspectives on the off-label use of anticancer drugs: an updated classification and exploration of categories - Chen, Xiaoyi; Ou, Shunlong; Luo, Jing; He, Zhisan; Jiang, Qian (Frontiers in Pharmacology, 2024)
To date, the definition that off-label usage of drugs refers to unapproved use of approved drugs, which covers unapproved indications, patient populations, doses, and/or routes of administration has been in existence for many years. Currently, there is a limited frequency and prevalence of research on off-label use of antineoplastic drugs, mainly due to the incomplete definition and classification issue. It's time to embrace new categories for off-label usage of anticancer drugs. This review provided insight into an updated overview of the concept and categories of off-label use for anticancer drugs along with illustrating specific examples to establish the next studies about the extent of off-label usage of anticancer drugs in the oncology setting further. The scope of off-label use of current anticancer drugs beyond the previous definitions, which include not only off-label uses in terms of indications, patient populations, doses, and/or routes of administration but also off-label use in terms of medication course, combination, sequence of medication, clinical purpose, contraindications scenarios, etc. Besides, the definition of off-label usage of anticancer drugs should be added to a condition of a given time and it varies by country. We presented a new and relatively comprehensive classification, providing extensive analysis and illustrative examples of the off-label usage of antineoplastic drugs for the first time. Such a classification has the potential to promote practical adoption and enhance management strategies for off-label use of antitumor drugs.